Investigation of the Ductile-to-Brittle Transition during Scratching of Polycrystalline Dual-phase γ-TiAl Alloy - Liu, Ailin (International Journal of Mechanical and Electrical Engineering, 2025)
This study investigates the ductile-to-brittle transition (DBT) in a polycrystalline dual-phase γ-TiAl alloy through a novel variable-depth, variable-speed scratch testing approach. Continuous grooves (0–40 μm) were created at scratching speeds of 500–4000 mm/min using a diamond conical indenter, with in-situ cutting forces monitored via a Kistler dynamometer and surface morphologies captured using synchronized 3D optical and confocal laser scanning microscopy. The results delineate three distinct deformation regimes: (1) ductile material removal (< 6–7 μm), characterized by smooth surfaces and stable forces; (2) a mixed-mode transition zone (6–14 μm), marked by microcrack initiation and periodic force oscillations; and (3) brittle-dominated fracture (> 14–16 μm), exhibiting extensive cracking and pronounced force fluctuations. Higher scratching speeds amplified force amplitudes and accelerated crack onset. Critical uncut chip thicknesses for DBT onset and completion were quantified at 6–7 μm and 14–16 μm, respectively. This work provides the synchronized mechanical–morphological analysis of DBT in γ-TiAl at the microscale, offering quantitative insights for optimizing high-speed micromachining processes and enhancing surface integrity in aerospace applications.